Examining the chemical composition of black carbon particles from biomass burning with SP-AMS. (June 2018) - Fortner, Edward; Onasch, Timothy; Canagaratna, Manjula; Williams, Leah R.; Lee, Taehyoung; Jayne, John; Worsnop, Doug
Abstract: We present laboratory measurements of the chemical speciation of black carbon particles produced from burning a series of biomass fuels during FLAME III (2009). A soot particle aerosol mass spectrometer (SP-AMS) was utilized to study the chemical composition of refractory black carbon particles and the associated nonrefractory components. We examine the effect of source fuel and combustion efficiency on the chemical composition of the emitted black carbon aerosol particles. Fifteen different source fuel types were examined. Two distinct types of black carbon spectra were observed: Low mass to charge (C1 + -C5 + ) black carbon cluster ions were observed for all fuels while high mass to charge (>C32 + ) black carbon cluster ions with distinctive fullerene structure were found for turkey oak and pine species. The relative ratios between the mass concentrations of non-refractory organic species and black carbon varied between fuel types and displayed an inverse correlation with the modified combustion efficiency (MCE) of the burns. Finally, positive matrix factorization (PMF) was conducted on the SP-AMS mass spectra in order to examine the variability in the chemical composition of the observed biomass burning particles and to identify potential signatures of different fuel types. Highlights: The chemical mass spectral signature of black carbon in biomass burning is examined. Organic mixtures on or within black carbon cores are examined with SP-AMS. Variation with fuel type of the chemical structure of core and mixture is examined.